Recycled coal bottom ash as sustainable materials for cement replacement in cementitious Composites: A review - Al Biajawi, Mohammad I.; Rahimah, Embong; Khairunisa, Muthusamy; Norasyikin, Ismail; Obianyo, Ifeyinwa I. (Elsevier Ltd, 2022)
In the current era, the engineering and construction sector has successfully participated in the challenge of utilizing sustainable, ecological, and recycled materials in concrete industrialization. Waste materials are mostly dumped into open areas and landfills, which leads to health hazards and environmental pollution. The use of recycled waste materials such as coal bottom ash (CBA) in the production of concrete or mortar is an ecological alternative. Due to the economic and environmental benefits of CBA, this study aims to critically review the work done on recycled CBA. To date, a total of 166 studies were reviewed to provide a comprehensive literature review. The CBA's chemical and physical properties can vary depending on the sources influenced by the production process. Other properties such as thermal conductivity and dry shrinkage were also reviewed. In particular, the effect of CBA on the mechanism of coal combustion. The CBA as a cement replacement material in cement composites can enhance fresh and mechanical properties on concrete or mortar up to a specific ratio. The finding shows that grinding CBA from coal can be used in concrete or mortar as a substitute material in violent environments. Overall, this study suggests the concept of turning a variety of wastes into useful resources. The goal is primarily to reduce the industry's enormous dependence on cement production to ultimately achieve a sustainable, valuable green environment in the pursuit of prosperity nationwide.